MERETAS URGENSI AUDIT KINERJA DALAM MENCIPTAKAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH KOTA/KABUPATEN - sugimin sugimin (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2018)
This article explains the urgency of an audits performance (value for money audits) in creating of performance accountability at cityor district government instance. This study was conducted by literature study with reference to a number of previous study and related regulations. The results of the study indicate that performance is a formal evaluation instrument for the government program. It helps to increase the public accountability by providing information concerning the government performance that may not be accessible to the public. The understanding of this concept and its implementation will enable to achieve optimal accountability for the public sector. It is concerned about performance audits centered on economic achievement, efficiency, and effectiveness depend on the existence of regulation, planning, assessment, authorization and control over the use of its resources. It is the responsibility of the public policy makers to establish the arrangements and to ensure that they are functioning appropriately. The responsibility of the internal auditor is to independently verify that execution of activities by policymakers have complied with the basic standards.